Pengaruh Aromaterapi Sebagai Alternatif Terapi Stress dan Kecemasan Pada Ibu Hamil - Maulia Azda; Afrina Zulaikha (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2026)
Pregnancy is a period marked by significant emotional challenges for expectant mothers, with stress and anxiety being common issues that may adversely affect maternal well-being and fetal development. The limited availability of safe treatment options for pregnant women, particularly concerning pharmacological interventions, has prompted the exploration of more natural and non-invasive therapeutic alternatives. One increasingly popular method is aromatherapy, which utilizes essential oils to stimulate the limbic system in the brain, thereby promoting relaxation and reducing anxiety. This study aims to explore the effects of aromatherapy in lowering stress and anxiety among pregnant women through a literature review. The method employed involves collecting and analyzing findings from previous studies regarding the use of aromatherapy in pregnancy. Based on the available evidence, aromatherapy—particularly with lavender essential oil—has been proven effective in lowering levels of stress and anxiety in pregnant women. Several studies report a reduction in anxiety levels of up to 40% following the inhalation of lavender oil. However, factors such as the type of essential oil used, the method of application, and individual sensitivity may influence therapeutic outcomes. Despite its potential benefits, the safety of aromatherapy use remains a concern, particularly regarding essential oils that may be unsafe for use during pregnancy.